Lipid Specific Membrane Interaction of Aptamers and Cytotoxicity - Md. Ashrafuzzaman; Hanouf A. M. AlMansour; Maha A. S. AlOtaibi; Zahid Khan; Gouse M. Shaik (Membranes, 2021)
We aim to discover diagnostic tools to detect phosphatidylserine (PS) externalization on apoptotic cell surface using PS binding aptamers, AAAGAC and TAAAGA, and hence to understand chemotherapy drug efficacy when inducing apoptosis into cancer cells. The entropic fragment-based approach designed aptamers have been investigated to inspect three aspects: lipid specificity in aptamers’ membrane binding and bilayer physical properties-induced regulation of binding mechanisms, the apoptosis-induced cancer cell surface binding of aptamers, and the aptamer-induced cytotoxicity. The liposome binding assays show preferred membrane binding of aptamers due to presence of PS in predominantly phosphatidylcholine-contained liposomes. Two membrane stiffness reducing amphiphiles triton X-100 and capsaicin were found to enhance membrane’s aptamer adsorption suggesting that bilayer physical properties influence membrane’s adsorption of drugs. Microscopic images of fluorescence-tagged aptamer treated LoVo cells show strong fluorescence intensity only if apoptosis is induced. Aptamers find enhanced PS molecules to bind with on the surface of apoptotic over nonapoptotic cells. In cytotoxicity experiments, TAAAGA (over poor PS binding aptamer CAGAAAAAAAC) was found cytotoxic towards RBL cells due to perhaps binding with nonapoptotic externalized PS randomly and thus slowly breaching plasma membrane integrity. In these three experimental investigations, we found aptamers to act on membranes at comparable concentrations and specifically with PS binding manner. Earlier, we reported the origins of actions through molecular mechanism studies—aptamers interact with lipids using mainly charge-based interactions. Lipids and aptamers hold distinguishable charge properties, and hence, lipid–aptamer association follows distinguishable energetics due to electrostatic and van der Waals interactions. We discover that our PS binding aptamers, due to lipid-specific interactions, appear as diagnostic tools capable of detecting drug-induced apoptosis in cancer cells.